2020
DOI: 10.1093/molbev/msaa193
|View full text |Cite
|
Sign up to set email alerts
|

Additive Uncorrelated Relaxed Clock Models for the Dating of Genomic Epidemiology Phylogenies

Abstract: Phylogenetic dating is one of the most powerful and commonly used methods of drawing epidemiological interpretations from pathogen genomic data. Building such trees requires considering a molecular clock model which represents the rate at which substitutions accumulate on genomes. When the molecular clock rate is constant throughout the tree then the clock is said to be strict, but this is often not an acceptable assumption. Alternatively, relaxed clock models consider variations in the clock rate, often based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 63 publications
1
33
0
2
Order By: Relevance
“…We estimated a mutation rate for this clade over the clonal frame to 1.02 × 10 −4 mutations per site per year. This mutation rate corresponds well with the rates reported for other S. enterica serovars ( Okoro et al., 2012 ; Hawkey et al., 2013 ; Octavia et al., 2015 ) and is similar to recent estimates following equivalent approximations ( Didelot et al., 2021 ).
Figure 4 Temporal signal in the Paratyphi C clade (A) Regression of the root-to-tip distance and collection date of the samples present in the tree, with 1 × 10 7 permutations.
…”
Section: Resultssupporting
confidence: 90%
“…We estimated a mutation rate for this clade over the clonal frame to 1.02 × 10 −4 mutations per site per year. This mutation rate corresponds well with the rates reported for other S. enterica serovars ( Okoro et al., 2012 ; Hawkey et al., 2013 ; Octavia et al., 2015 ) and is similar to recent estimates following equivalent approximations ( Didelot et al., 2021 ).
Figure 4 Temporal signal in the Paratyphi C clade (A) Regression of the root-to-tip distance and collection date of the samples present in the tree, with 1 × 10 7 permutations.
…”
Section: Resultssupporting
confidence: 90%
“…Depending on the data, variations of the relaxed clock model, such as the fixed local clock, whereby the underlying tree has a constant rate, but the rate of each clade is able to differ from this global rate [ 99 ]; the uncorrelated relaxed clock, whereby each branch of the tree is allowed its own mutation rate independent of the rate on neighbouring branches [ 98 ]; or the random local clock, which forms an interim between the strict and relaxed clocks, where each branch can take a different rate or remain the same as one another [ 100 ]. More recently, additive clock models have been proposed that satisfy the additive property often unsatisfied by conventional relaxed clock models [ 101 ] and may in most cases be more appropriate than the conventional relaxed clock. In the fungal studies identified, both C. auris papers (Chow and Rhodes) utilised strict clock models, seemingly without comparison with alternative options.…”
Section: Methodological Considerations For Temporal Analyses Of Pathogenic Fungimentioning
confidence: 99%
“…The systematically subsampled data set was analysed with BEAST v1.10.5 (https://github.com/beast-dev/beast-mcmc/releases/tag/v1.10.5pre_thorney) using a newly implemented method that estimates the tree likelihood at each point of the MCMC chain. This approach takes a data tree (the aforementioned re-rooted ML tree) instead of an alignment and significantly reduces analysis time by using a simple model to rescale the ML phylogeny into a time-calibrated tree (see 38). Under this approach, the likelihood of each branch length is defined as a function of a Poisson distribution with a mean directly proportional to the clock rate (38,39); we therefore used a rate of 6.28x10 -4 substitutions/site/year, based on the median clock rate estimate obtained from our exploratory analysis.…”
Section: Phylogenetic Identification Of Transmission Lineagesmentioning
confidence: 99%
“…This approach takes a data tree (the aforementioned re-rooted ML tree) instead of an alignment and significantly reduces analysis time by using a simple model to rescale the ML phylogeny into a time-calibrated tree (see 38). Under this approach, the likelihood of each branch length is defined as a function of a Poisson distribution with a mean directly proportional to the clock rate (38,39); we therefore used a rate of 6.28x10 -4 substitutions/site/year, based on the median clock rate estimate obtained from our exploratory analysis. We also defined a coalescent Skygrid prior, similar to the one described for the exploratory analysis.…”
Section: Phylogenetic Identification Of Transmission Lineagesmentioning
confidence: 99%